2003
DOI: 10.1590/s1415-47572003000300014
|View full text |Cite
|
Sign up to set email alerts
|

Population structure analysis of Pimelodus maculatus (Pisces, Siluriformes) from the Tietê and Paranapanema Rivers (Brazil)

Abstract: Pimelodus maculatus populations from the Tietê and Paranapanema rivers were sampled and had their genetic structure analyzed by using RAPD markers, with the aim of contributing to future conservation studies. The proportion of polymorphic loci was greater than 50% in the populations of both rivers. Genetic diversity data showed that, in spite of its nine hydroelectric plants, the Tietê river population was genetically homogeneous, whereas the Paranapanema river population was structured. This might be due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 10 publications
0
47
0
4
Order By: Relevance
“…The highestP and H E values were observed in A. altiparanae and the lowest values in L. amblyrhynchus (Table 2). All levels of genetic diversity in the populations studied here were evaluated as satisfactory compared to previously reported data (Chiari and Sodré, 2001;Almeida et al, 2003;Leuzzi et al, 2004;Pamponet et al, 2008). …”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The highestP and H E values were observed in A. altiparanae and the lowest values in L. amblyrhynchus (Table 2). All levels of genetic diversity in the populations studied here were evaluated as satisfactory compared to previously reported data (Chiari and Sodré, 2001;Almeida et al, 2003;Leuzzi et al, 2004;Pamponet et al, 2008). …”
Section: Discussionmentioning
confidence: 62%
“…Previous studies using RAPD reported the following values ofP: Schizodon intermedius 45.5%, Schizodon nasutus 41.4%, Leporinus amblyrhynchus 29.3%, Leporinus friderici 46.3%, Leporinus striatus 41%, Leporinus octofasciatus 55.1%, Leporinus elongatus 58.7%, and Leporinus obtusidens 53.1% (Chiari and Sodré, 2001); Astyanax altiparanae 78.41% (Leuzzi et al, 2004), Astyanax aff. bimaculatus 85.71% (Pamponet et al 2008), Pimelodus maculatus 50.1-60.94% (Almeida et al, 2003), and Steindachnerina insculpta 76.6% (Oliveira et al, 2002). By comparison, we foundP values of 82.0% to 30.5%, and H E levels of 0.312 to 0.122 in the five species studied here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Lacépède,1803), order Siluriformes, family Pimelodidae. Almeida et al (2003) performed studies in the P. maculatus population structure for the Tietê and Paranapanema Rivers and obtained genetic identity values around 0.96 for the Tietê and 0.91 for the Paranapanema River. These values were similar to those reported by Thorpe and Solé-Cava (1994), who found that 98% of the populations of the same species showed a genetic identity higher than 0.85.…”
Section: Discussionmentioning
confidence: 99%
“…Informations derived from molecular genetic techniques shall contribute significantly for the preservation of aquatic genetic resources and sustainable development (Carvalho, 1993;Chiari, 1999;Martins et al, 2003;Almeida et al, 2003). The RAPD procedure (Randomly Amplified Polymorphic DNA) has been instrumental to understand the genetic variability of fish populations (Bielawski and Pumo, 1997;Caccone et al, 1997;Callejas and Ochando, 1998;Dergam et al, 1998;Nadig et al, 1998;Liu et al, 1999;Prioli et al, 2002;Shikano and Taniguchi, 2002;Almeida et al, 2003;Bártfai et al, 2003;Hatanaka and Galetti Jr, 2003). This technique consists of amplification by PCR (Polymerase Chain Reaction) of random segments of genomic DNA using a single short primer of arbitrary sequence.…”
Section: Introductionmentioning
confidence: 99%